Cognitive and psychosocial features of childhood and juvenile MS - Amato, M P; Goretti, B; Ghezzi, A; Lori, S; Zipoli, V; Portaccio, E; Moiola, L; Falautano, M; De Caro, M F; Lopez, M; Patti, F; Vecchio, R; et al. (Neurology, 2008)
To assess the impact of multiple sclerosis (MS) on cognitive and psychosocial functioning in childhood and juvenile cases. We used an extensive neuropsychological battery assessing IQ, memory, attention/concentration, executive functions, and language. Fatigue and depression were also measured. An interview on school and daily living activities was obtained from the parents. Performance of cases was compared with that of demographically matched healthy controls. Sixty-three patients and 57 healthy controls were assessed. Five patients (8%) exhibited a particularly low IQ (<70). Criteria for cognitive impairment (failure on at least three tests) were fulfilled in 19 patients (31%), whereas 32 patients (53%) failed at least two tests. Beyond deficits in memory, complex attention, and executive functions, the profile of deficits was characterized by involvement of linguistic abilities. In the regression analysis, the only significant predictor of cognitive impairment was an IQ score lower than 90 (odds ratio [OR] 18.2, 95% CI 4.6-71.7, p < 0.001). Considering the IQ score as a dependent variable, the only significant predictor was represented by younger age at onset (OR 0.7, 95% CI 0.5-0.9, p = 0.009). Depressive symptoms were reported by 6% of the cases, and fatigue was reported by 73% of the cases. MS negatively affected school and everyday activities in 56% of the subjects. In childhood and juvenile cases, multiple sclerosis (MS) is associated with cognitive impairment and low IQ scores, the latter related to younger age at onset. These aspects are of critical importance in helping children and adolescents with MS to manage their difficulties and psychosocial challenges.